2012
DOI: 10.6061/clinics/2012(06)07
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-gamma and interleukin-10 production by mononuclear cells from patients with advanced head and neck cancer

Abstract: OBJECTIVE:This study aims to evaluate the production of interferon-gamma and interleukin-10 by stimulated peripheral blood mononuclear cells isolated from patients with supraglottic laryngeal cancer before and after surgical treatment.METHODS:Fourteen patients with advanced supraglottic laryngeal cancer were studied. Cultures of peripheral blood mononuclear cells isolated during the preoperative and late postoperative periods were stimulated with concanavalin A and Bacille Calmette-Guérin, and the supernatant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
(13 reference statements)
1
7
0
1
Order By: Relevance
“…While these results can explain equal IFNg production in HNSCC and HD T cells, the increase in IFNg in HNSCC T cells may be due to enhanced TCR signaling upstream to ion channels. A robust increase in IFNg in activated HNSCC lymphocytes (4-fold higher than in HD) was previously reported by others (Conti-Freitas et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…While these results can explain equal IFNg production in HNSCC and HD T cells, the increase in IFNg in HNSCC T cells may be due to enhanced TCR signaling upstream to ion channels. A robust increase in IFNg in activated HNSCC lymphocytes (4-fold higher than in HD) was previously reported by others (Conti-Freitas et al, 2012).…”
Section: Discussionsupporting
confidence: 83%
“…42 Given the high CD137 RNA levels in HPV+ HNSCC samples, we expected higher effector cytokine production by T-cells in these samples. Indeed, HPV+ HNSCC expressed significantly higher levels of IFN-γ, granzyme A, granzyme B, and perforin compared to HPV- HNSCC or normal control samples, indicating that there remains some T-cell effector functionality in these tumors.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, a negative correlation between circulating levels of IL-10 and prognosis has been reported. 24 In the present study, we showed for the first time that IL-10 is the major mediator inducing EMT of pancreatic cancer cells, implying a potent target regarding to regulation of M2-polarized TAMs in tumor microenvironment.…”
Section: M2-polarized Tams Promoted Emt Of Pancreatic Cancer Cells C-mentioning
confidence: 92%